Role of Incretin Axis in Inflammatory Bowel Disease - Duan, Lihua; Rao, Xiaoquan; Braunstein, Zachary; Toomey, Amelia C.; Zhong, Jixin (Frontiers in Immunology, 2017)
The inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC), are chronic inflammatory conditions of the gastrointestinal tract and involve a complicated reciprocity of environmental, genetic, and immunologic factors. Despite substantial advances in the foundational understanding of the immunological pathogenesis of IBD, the detailed mechanism of the pathological progression in IBD remains unknown. In addition to Th1/Th2 cells, whose role in IBD has been previously well defined, recent evidence indicates that Th17 cells and Tregs also play a crucial role in the development of IBD. Diets which contain excess sugars, salt, and fat may also be important actors in the pathogenesis of IBD, which may be the cause of high IBD incidence in western developed and industrialized countries. Up until now, the reason for the variance in prevalence of IBD between developed and developing countries has been unknown. This is partly due to the increasing popularity of western diets in developing countries, which makes the data harder to interpret. The enterocrinins glucagon-like peptides (GLPs), including GLP-1 and GLP-2, exhibit notable benefits on lipid metabolism, atherosclerosis formation, plasma glucose levels, and maintenance of gastric mucosa integrity. In addition to the regulation of nutrient metabolism, the emerging role of GLPs and their degrading enzyme dipeptidyl peptidase-4 (DPP-4) in gastrointestinal diseases has gained increasing attention. Therefore, here we review the function of the DPP-4/GLP axis in IBD.